The liberation movements in Angola and the creation of the Angolan Armed Forces: contributions from the political ideology (Tempo e Argumento, 2021)
As relevant as characterizing an Armed Forces at the present, and designing their future, based on their leadership, military capabilities, technical valences, tactics, and technology, and obviously their operationality, it is important to look at their past and see what influences had, from which derives their political ideology, which History is in its genesis and that represent in its nationalism. This article summarizes and try to seek to identify, in a chronological and matrix way, all these factors that contributed in Angola to the creation of the Angolan Armed Forces and which are the identity matrix of Angola and the People of Angola.Keywords: Angola; liberation movements; Angolan armed forces; security and defense.